Desain Bahan Ajar Bahasa Berbasis Project Based Learning dengan Kearifan Lokal Bima untuk Melatih Keterampilan Membaca Siswa - Muslimin Muslimin; Nurdiniawati Nurdiniawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is motivated by problems in teaching Indonesian language at junior high schools, particularly in reading skills. To address these issues, a Project-Based Learning (PjBL) teaching material integrating Bima’s local wisdom was designed to improve students’ reading skills. The study aims to design PjBL-based teaching materials that incorporate Bima’s local wisdom to foster students’ reading abilities and to evaluate their feasibility in enhancing reading skills. This is a Research and Development (R&D) study employing the Borg & Gall model, consisting of several stages: preliminary study, initial draft preparation, validation and revision, limited trials, product revision, field trials, further revisions, and product dissemination. This article presents the validation results from material experts, media experts, teachers, and trials with students at SMP IT Al Mahmud Keli, assessed using a Likert scale. The research resulted in Indonesian language teaching materials based on Project-Based Learning (PjBL) integrated with Bima’s local wisdom to improve junior high school students’ reading skills. The research process was systematically conducted through needs analysis, curriculum analysis, and student characteristics analysis. The design was validated by material and media experts, showing feasibility percentages above 90%, and revised based on suggestions to make it more contextual and engaging. Limited and large-scale field trials confirmed that the teaching material is clear, easy to understand, attractive, and enhances student engagement in reading activities. The average student response reached 89.41%, categorized as very feasible, while teacher responses showed a feasibility percentage of up to 98%. Thus, the PjBL-based teaching materials with Bima’s local wisdom are proven feasible, effective, and innovative to support students’ reading literacy while instilling cultural values.